PENGARUH PANDEMI COVID-19 TERHADAP RISIKO PEKERJAAN KONSTRUKSI DI KOTA PADANG - Wendi Boy; Deni Irda Mazni; Gusni Vitri; Gito Rahman (Teknika, 2022)
The Province of West Sumatra, especially the City of Padang, before the COVID-19 pandemic was actively building housing that really helped the community in the availability of decent housing. The COVID-19 pandemic has caused a decline in the number of construction projects across the country, including housing developments. So in this study, we want to know about the influence of COVID-19 on the risk of work carried out in the construction world in the city of Padang, especially in housing construction. The results of the study contained 8 risk factors for delays (material factors); labor factors (labors); equipment factors (equipment); financial factors (financing); environmental/situation factors (environment); regional restriction factors (PSBB/PPKM); Site characteristics, managerial factors and 57 risk variables for housing construction during the COVID-19 pandemic that affected work delays, found the 10 highest risks. Strategies that can be applied to the implementation of Housing Construction Projects during the pandemic and post-pandemic, are adjusted to the main factors that are formed. For the first Main component, the solutions that can be applied include: 1) Controlling the Project cash flow effectively and efficiently; 2) Application of the method of analysis of the value of the results (earn value method) to control the project budget and time; 3) Prepare project unexpected budgets; 4) Apply strict health protocols to ongoing projects